Effect of Frying Combined with Roasting on the Quality of Roasted Green Tea - ZHANG Rongxiang, DU Yaru, ZHANG De, DONG Zhijie, NI Dejiang, ZHENG Shibing, YU Zhi (Shipin Kexue)
In this study, fresh tea shoots, one bud with two or three leaves, from a tea garden in Wujiatai village of Xuan’en County, Hubei Province were processed into roasted green tea. An orthogonal array design was employed to investigate the impact of roller frying temperature, the amount of tea shoots fed to the drum, and the residual water content after frying on the quality of roasted green tea. The roller frying parameters were optimized using principal component analysis (PCA). The results revealed that five principal components (PCs) were extracted in PCA performed on 32 physicochemical indexes, which together explained 90.06% of the total variance. Using the comprehensive evaluation function and main effect analysis, the optimum processing parameters were obtained as follows: roller roasting temperature (150 ± 5) ℃, feeding 2 kg of tea shoots, and retention of 25% water after frying. Compared with green tea samples without roller frying treatment, the sensory scores for appearance, aroma, taste and waste of roasted green tea with roller frying were higher, and the astringency was reduced. Additionally, roller frying improved the uniformity and tightness of tea strips. This study demonstrated that introducing roller frying to the tea-making process could enhance the quality of roasted green tea.